Oral therapy of recombinant Subtilisin QK-2 potentiates thrombolytic effect in a carrageenan-induced thrombosis animal model. (January 2022) - Tang, Yiping; Yang, Yuanyuan; Lu, Xuan; Liu, Qiuchen; Li, Qiaohong; Song, Xia; Wang, Man; Hu, Hankun; Zhou, Li; Wang, Yefu
Graphical abstract: Highlights: rSubtilisin QK has been shown to be resistant against pancreatic enzyme mimics. rSubtilisin QK can be transferred into the bloodstream and all organs via intestinal absorption. D-dimer and FDP levels elevated following rSubtilisin QK oral administration. rSubtilisin QK has thrombolytic effects by oral gavage in vivo . t-PA expression was increased by rSubtilisin QK, while PAI-1 showed the opposite trend. Abstract: Thrombosis is a severe health care issue and one of the leading causes of death globally. Since presently used drugs have a number of limitations, safe and effective thrombolytic agents are still needed. Subtilisin QK, widely used as a component of functional food, presents high direct cross-linked fibrin degradation, without activation of plasminogen. It could be absorbed throughout intestine and infiltrate into all organs with fibrinolytic activity against the pancreatic enzyme and acidic pH mimicking the stomach in a time-dependent manner. Oral intake of rSubtilisin QK also elevated levels of fibrin/fibrinogen degradation products, D-dimer, and tissue plasminogen activator (t-PA) in plasma, and alleviated ear- and tail-thrombosis in κ-carrageenan-induced model. Furthermore, the levels of t-PA were increased in cultured HUVECs stimulated with rSubtilisin QK, while plasminogen activator inhibitor-1 showed the opposite trend simultaneously, suggesting the activation of plasminogen. In conclusion, rSubtilisin QK exerted thrombolytic effects in vivo and may be a potential oral thrombolytic agent.